KAJIAN PEMANFAATAN PATI MODIFIKASI METODE FISIK PADA PEMBUATAN TODDLER COOKIES PREBIOTIK - Dewi Cakrawati; Siti Mujdalipah (AGROINTEK, 2014)
New type of cookies has been made by wild yam (gembili) flour to substitute wheat flour.  Starch from gembili (wild yam) contains dietary fiber that can support probiotic growth. The use of gembili starch to substitute wheat flour cookies for toddler is expected to improve the content of dietary fiber in toddler cookies, so that toddlers’ gastrointestinal function is improved. Research on the effect of modified starch in prebiotic toddler gembili cookies was conducted by employing an experimental design of Split Plot Design with two factors: methods of starch modification which were pre gelatinization and autocalving-cooling, and substitution rate of gembili starch (10%,20%,30%,40%). Organoleptic analysis using hedonic quality test showed treatment accepted by panelis was autoclaving-cooling starch with 20% substitution rate containing 6.11% of dietary fiber.